Hypophysotropic activity of histone H3 in vitro - Brown, Oscar Alfredo (2003)
To assess the effect of histoneH3on pituitary hormone secretion, rat anterior pituitary (AP) cells were used and growth hormone, prolactin, thyrotropin, luteinizing hormone and follicle stimulating hormone measured by radioimmunoassay. Incubation of cells with H3 (1, 6, and 30mM) stimulated the release of all five hormones in a dose-dependent manner. This effect was blocked by preincubation of H3 with an anti-H3 antibody. Incubation of AP cells with 6mMH3 in the presence of specific AP hormone secretagogues (GRP-6, thyrotropin-releasing hormone (TRH), gonadotropin-releasing hormone (GnRH)) showed additive effects on hormone secretion. Pharmacological experiments suggested that calcium- and diacylglycerol- (DAG) associated pathways, but not cAMP, participate in the hypophysiotropic activity of H3. Our results confirm previous evidence that histones may act as hypophysiotropic signals.